2008
DOI: 10.1530/rep-07-0369
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin-inhibitory hormone (GnIH) receptor gene is expressed in the chicken ovary: potential role of GnIH in follicular maturation

Abstract: Gonadotropin-inhibitory hormone (GnIH), an RFamide peptide, has been found to inhibit pituitary LH secretion in avian and mammalian species. The gene encoding a putative receptor for GnIH (GnIHR) was recently identified in the chicken and Japanese quail brain and pituitary gland. GnIHR appears to be a seven-transmembrane protein belonging to a family of G-protein-coupled receptors. In the present study, we have characterized the expression of GnIHR mRNA in the chicken ovary and demonstrate that GnIHR may exert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
66
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 33 publications
7
66
0
Order By: Relevance
“…Because receptors for GnIH are also expressed in gonadal tissue of birds (29) and rhesus monkey (Macaca mulatta) (47), there is a potential for a highly localized autocrine or paracrine effect of GnIH on gonads. GnIH-R mRNA have been localized in the theca and granulosa cells, with significantly lower levels found in preovulatory follicles than in smaller growing follicles (30). The earlier finding showing presence of GnIH-R in the ovary together with the findings of present in vivo and in vitro study suggests intraovarian effects of GnIH in mice.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Because receptors for GnIH are also expressed in gonadal tissue of birds (29) and rhesus monkey (Macaca mulatta) (47), there is a potential for a highly localized autocrine or paracrine effect of GnIH on gonads. GnIH-R mRNA have been localized in the theca and granulosa cells, with significantly lower levels found in preovulatory follicles than in smaller growing follicles (30). The earlier finding showing presence of GnIH-R in the ovary together with the findings of present in vivo and in vitro study suggests intraovarian effects of GnIH in mice.…”
Section: Discussionsupporting
confidence: 62%
“…Whether these effects of GnIH on testes are exerted through suppression of pituitary gonadotropin synthesis and/or they are due to direct action of GnIH on testes is not clear. Recent studies indicate that the avian reproductive system (female and male gonads, epididymis) has the capability to synthesize and bind GnIH (29,30).…”
mentioning
confidence: 99%
“…The presence of GnIH-R has been detected in the testes and ovaries of several vertebrate species, including birds (McGuire and Bentley, 2010), and putative GnIH binding sites have been demonstrated in the granulosa cell layer by receptor fluorography in birds . GnIH-R mRNA has been localized in the theca and granulosa cells, with significantly lower levels found in preovulatory follicles than in smaller growing follicles (Maddineni et al, 2008). Singh et al (2011) has demonstrated the direct inhibitory effect of GnIH on ovarian steroidogenesis in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, variations within genes have important effects on biological traits. Previous studies on the chicken genome have shown higher GnIH expression at sexual maturity in chicken ovaries, diencephalon (Maddineni et al, 2008b), and follicular maturation (Maddineni et al, 2008a). In the chicken hypothalamus, pituitary, ovary, and oviduct, GnIH mRNA expression of broody and after brooding chickens was higher than that of laying hens (He, 2009).…”
Section: Discussionmentioning
confidence: 85%